Post‐Release Mortality of European Bass ( Dicentrarchus labrax ) Discarded From Small‐Scale Estuarine Fishing - J. E. Stewart; T. Stamp; P. Davies; A. Hall; T. Robbins; L. Stewart; E. V. Sheehan (Fisheries Management and Ecology, 2026)
Estuaries provide essential habitats for many fish species, but their confined and accessible nature may increase fish vulnerability to capture, and few empirical studies have quantified the value of restricting net fisheries in such areas. Furthermore, management measures for some fisheries promote discarding (e.g., of European sea bass; Dicentrarchus labrax ), yet the mortality of fish discarded from small‐scale inshore fisheries is poorly understood. We used condition assessments, Reflex Action Mortality Predictor scores and acoustic tracking to evaluate post‐release mortality of bass captured in small‐scale estuarine netting and angling. Gillnet‐caught bass exhibited a range of stress responses and 20%–24% mortality shortly after capture, whereas angler‐caught bass showed no short‐term post‐release mortality. Six‐month survival of fish released in good condition was > 80% for both gear types. However, strong site fidelity and residency were observed which could increase recapture risk. Our findings underscore the potential benefits of prohibitions of netting in sensitive estuaries and can inform fisheries discards management.